Biomass production carbon storage capacity and nutrient export in natural rubber - Ambily K K; Ulaganathan A (Rubber Board Bulletin, 2015)
Assessment of biomass, nutrient accumulation and carbon stock are important in the cultivation of long duration plantation crops like rubber (Hevea brasiliensis) for beneficial managements in terms of economic and environmental sustainability of the ecosystem. Three rubber trees of clones RRII 105, RRII 203 & GT 1 at the age of 30 years, grown on a sandy clay loam Ultisol were destructively sampled to estimate the biomass production , nutrient export through the accumulated biomass and carbon storage. The trees were uprooted and fresh weight of each plant parts were recorded. A portion of the subsamples was oven dried to estimate the biomass and nutrient content. Results of the study indicated the total dry biomass (1140-2045 kg/tree), carbon stock (479-860 kg/tree) carbon storage potential (148-258 T carbon/ha) for three rubber clones at the age of 30 years. The average nutrient export due to biomass removal was estimated and found to be N = 1555.4, P = 201.5, K = 1700.5, Ca = 3292.8 Mg = 573.2 and Zn = 5.89, Cu = 2.63, Fe = 108.07 & Mn = 17.67 kg/ha in each planting cycle of 30 years period. Timber yield in rubber ranged from 556-949 kg/tree. Study reveals that the economic return in forms of timber and the environmental protection by higher carbon storage capacity are promising in rubber plantations. However, the nutrient export through biomass removal may be compensated with additional nutrition and proper management to sustain the soil productivity. Removal of potassium, calcium, magnesium and nitrogen was high as compared to phosphorous. Very less removal (178.6-226 kg/ha) of phosphorous was observed in rubber. Among micronutrients, removal was more for Fe & mn.
Keywords: Biomass; Carbon storage capacity; Nutrient export